The Role of Prosody and Intonation in English Phonology: Implications for Speech Perception and Production - Laila Anum; Zahwa Nazhifah Limbeng; Fara Audina Lubis; Adinda Dea Nazhira; Yani Lubis (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The role of prosody and intonation in English phonology has significant implications for speech perception and production. These phonological processes influence how words are understood and articulated in English. Recent studies have shown that prosody and intonation play a crucial role in verbal communication. This article aims to investigate the importance of prosody and intonation in understanding and producing speech in English language learning intonation refers to the melodic pattern in speech that can change the meaning of a sentence. It is often used to convey emotions or to emphasize a message. On the other hand, prosody encompasses the patterns of pitch, stress, and duration in speech that impact word articulation and comprehension. Both work together to create accurate articulation and understanding of words in English this linguistic study underscores the importance of prosody and intonation in English language learning and elucidates how these two aspects influence speech perception and production. With a deep understanding of prosody and intonation, learners can enhance their ability to communicate in English more effectively and accurately.